If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -12) = 38 Reorder the terms: x + (-12 + x) = 38 Remove parenthesis around (-12 + x) x + -12 + x = 38 Reorder the terms: -12 + x + x = 38 Combine like terms: x + x = 2x -12 + 2x = 38 Solving -12 + 2x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = 38 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = 38 + 12 2x = 38 + 12 Combine like terms: 38 + 12 = 50 2x = 50 Divide each side by '2'. x = 25 Simplifying x = 25
| 2(4w-6)= | | 3x+5(6x-8)=2 | | 9x*x-25=0 | | 2/4=v/6 | | -5(4p-2)= | | -3/n | | 18x*x+15x-12=0 | | 3(3+5)=12 | | C(t)=t^2-10+110 | | -3m-6=12 | | 3r-42=21 | | 4/36.2 | | 2w^2+3w=20 | | 3x-6=22-4x | | 3(2)+6(3)=24 | | A=26000+200x | | (6/10x)1/3=4 | | -5(4z-1)= | | (6/10x)1/3=4.536.000 | | 3(3)+6(3)=24 | | 2x^2-5x=-8 | | 21n=8064 | | -2/3x=5/8 | | (6/10x)1/3 | | 2x^3/2*6x^4/5 | | -2(6t)= | | 6x-12=12x+6 | | 5(2z-4)= | | 2(r-1)-3=5 | | 5-(3+2)+35= | | Ln(3y-5)=2ln(y-1)-ln(y-1) | | 11(-12-18x)+2(-4-17x)= |